THE RELATIONSHIP BETWEEN RESILIENCE AND CULTURE SHOCK IN STUDENTS FROM 3T REGIONS IN SALATIGA - Dano, Sarni Destomawati; Huwae, Arthur (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2025)
Socio-cultural changes experienced by students from out-of-town areas are a social phenomenon called culture shock. Culture shock causes individuals to experience anxiety and frustration about the events they experience, and one of the factors predicted to be related to increasing or decreasing culture shock is resilience. The purpose of this study was to determine the relationship between resilience and culture shock in out-of-town students from out-of-town areas in Salatiga. The method used was quantitative with a cross-sectional bivariate correlational design. The research participants were 60 students from out-of-town areas in Salatiga using the accidental sampling technique. The measurement used a resilience scale (? = 0.926) and a culture shock scale (? = 0.905). The results of the study proved that resilience was significantly negatively related to culture shock (r = -0.773 and sig. 0.000; p <0.01). This means that when there is an increase or decrease in resilience, it will be followed by a decrease or increase in culture shock in out-of-town students from out-of-town areas in Salatiga.